THE INFLUENCE OF THE @PEDULIJILBAB INSTAGRAM ACCOUNT ON FOLLOWERS' PERCEPTIONS OF HIJAB - Rahmawati, Fina; Ernawati, Erna; Lestari, Hana (JURNAL SAHID DA'WATII, 2022)
This research discusses the influence of the Instagram account @PeduliJilbab on the perception of wearing hijab followers. The purpose of this study was to determine how much correlation and influence the contribution of the @pedulijilbab Instagram account to the perception of followers' hijabs. The type of research used in this research is quantitative research with correlational methods, while the correlational methods are correlation and simple regression. This study shows the results of the calculation of the correlation of 0.481 means that it has a positive relationship with a moderate level. The regression calculation results show a significant positive effect of 0.000 while the contribution of Instagram accounts to perception is 17.5%.